Pengaruh Metode Tartil terhadap Kemampuan Membaca Al-Qur'an pada Mata Pelajaran PAI di SD Negeri 29 Dadok Tunggul Hitam - Rahayu, Fatimah (Lembaga Yasin AlSys, 2024)
This research aims to determine the influence and implementation of the tartil method on the ability to read the Qur'an at SD Negeri 29 Dadok nggump Hitam. This research uses a quantitative approach using SPSS version 25 software. The population of children in grades IV and V and the researchers took a total of 51 students. Data collection used tests, namely oral and written tests, observation and documentation. Data analysis uses relative frequency, normality test, homogeneity test, T test and hypothesis test. The results of the research show that H0 is rejected and Ha is accepted using the T test (Paired Sample T-Test) at a significance level of 5%, the t value is greater than the t table -8.100 > 2.064 and the significance value is 0.000 < 0.05, with t count > t table and sig < 0.05. Researchers obtained a post-test score in the control class of 83.62, in the experimental class it was 86.133. In the experimental class there was a difference in the average post-test score of 2.513. The results show that applying the Tartil approach improves students' ability to read the Koran, this can be seen from students in the experimental class having better performance than students in the control group who did not apply this method.